2012
DOI: 10.1007/s10409-012-0164-x
|View full text |Cite
|
Sign up to set email alerts
|

Tunable band structures of polycrystalline graphene by external and mismatch strains

Abstract: Lacking a band gap largely limits the application of graphene in electronic devices. Previous study shows that grain boundaries (GBs) in polycrystalline graphene can dramatically alter the electrical properties of graphene. Here, we investigate the band structure of polycrystalline graphene tuned by externally imposed strains and intrinsic mismatch strains at the GB by density functional theory (DFT) calculations. We found that graphene with symmetrical GBs typically has zero band gap even with large uniaxial … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…Analogously, we observe the maximum band gap opening up for cases where the original band structure showed the maximal tilt along the (1, 1, 1) direction. This matches Weyl semimetal studies where it has been shown that lifting the degeneracy in a fully centrosymmetric Weyl semimetal is difficult 42 . It has also been shown that tilted Weyl semimetals have a better response to light, and they can support significant photocurrents while centrosymmetric Weyls cannot 43 .…”
Section: B Changes In the Band Structuresupporting
confidence: 88%
“…Analogously, we observe the maximum band gap opening up for cases where the original band structure showed the maximal tilt along the (1, 1, 1) direction. This matches Weyl semimetal studies where it has been shown that lifting the degeneracy in a fully centrosymmetric Weyl semimetal is difficult 42 . It has also been shown that tilted Weyl semimetals have a better response to light, and they can support significant photocurrents while centrosymmetric Weyls cannot 43 .…”
Section: B Changes In the Band Structuresupporting
confidence: 88%
“…when the stress component in the transverse direction is fully relaxed to be zero, remains unknown. Furthermore, it is recognized that the presence of defects in graphene can significantly alter the mechanical and electrical properties of graphene [25][26][27][28]; therefore, it is critical to understand how defects affect the properties of h-BN if these defects present in h-BN. In this work, we perform a systematic investigation on several critical mechanical properties of single-layer h-BN, including Young's modulus, the Poisson's ratio, bending rigidity, the mechanical properties of h-BN with antisite defects and the band structure tunability by mechanical strain.…”
mentioning
confidence: 99%
“…As a matter of fact, the determining factor is the adsorption location, which means that similar features should be seen with impurities that have the same bonding geometry as hydrogen, i.e., top-bonded impurities. It is well known that realistic graphene samples have a multitude of surface effects such as ripples and corrugations [44,45], and that certain defects can modify the electronic structure and the chemical doping of graphene [46][47][48]. While the calculations with hydrogen in this work show a slight decrease in the binding energy of hydrogen between pristine and strained graphene, it is a possibility that other impurities and/or strain profiles could produce enhanced chemical doping.…”
Section: Discussionmentioning
confidence: 63%